Estudo analítico de um demonstrador da tecnologia da combustão supersônica - Carneiro, Ramon (2020)
The hypersonic airbreathing propulsion based on supersonic combustion (scramjet technology) has high potential to be use as intermediate stage for the aerospace vehicles. Using the atmospheric air as the working fluid and source of oxygen, they do not need to store the oxidant on-board, which results in lighter and more economical vehicles. An aerospace vehicle that flies at hypersonic velocities using scramjet technology requires a highly integrated system with no moving parts, where the propulsion system and the vehicle are indistinguishable. The inlet of the scramjet contributes to the compression of atmospheric air, up to necessary conditions for supersonic combustion in the combustion chamber, while the outlet of the scramjet contributes to the expansion of gases and thrust generation. This work is a theoretical analytical project (engineering approach) of a scramjet technology demonstrator designed to integrate a three-stage hypersonic accelerator vehicle, associated with the Brazilian rocket engines S30 and S31, and configured to demonstrated the supersonic combustion at an altitude of 30 km and velocity of 2051 m/s (corresponding to Mach number 6,8) using hydrogen fuel. One-dimensional analytical approach was used, where the main theories, that describe the fluid dynamic and thermodynamic processes of the compression, combustion and engine expansion sections, were applied. It was proposed to design the components of the scramjet using optimizations for operational advantages. The objective was obtain a compression system capable to compress the airflow to high temperature levels to auto-ignite, in the combustion chamber, the injected fuel (hydrogen). In the expansion section, was investigated the expansion angle capable to guarantee pressure at the trailing edge of the vehicle, equal to the freestream at the design altitude of 30 km (1197 Pa), according to the opened Brayton cycle. As global assessment of the behavior of the designed scramjet, the thermodynamic properties and velocities of a flow streamline that passes through the leading edge to the trailing edge of the vehicle were evaluated and the uninstalled thrust were calculated as a performance parameter. In the combustion section, two approaches were evaluated: the first disregarding the fuel injection in the combustion chamber (power-off), resulting in a configuration unable to produce positive thrust, with gradual vehicle deceleration. In the second approach, the injection of hydrogen at sonic velocity into the combustion chamber (power-on) was considered, which predicts spontaneous fuel burning and thermal energy addition to the system. For this case, the analytical results indicated positive thrust, corroborating to affirm that the scramjet engine has the propulsion capacity to the projected vehicle. For a more realistic analysis, the viscous flow effects were considered. The boundary layer thickness of the leading edge of the vehicle to the trailing edge of the vehicle was estimated and design modifications were proposed to accommodate it, such as the cowl repositioning, new compression ramp angles and the increase the height of the combustion chamber. The presence of the boundary layer modified the flow's thermodynamic properties, representing an advantage to guarantee the auto-ignition of the fuel in the combustion chamber. However, it reduced the propulsive capacity of the vehicle by decreasing the flow velocity at the trailing edge of the vehicle.